1993
DOI: 10.1111/j.1476-5381.1993.tb13996.x
|View full text |Cite
|
Sign up to set email alerts
|

Different pathways of calcium sensitization activated by receptor agonists and phorbol esters in vascular smooth muscle

Abstract: 1 It has been shown that receptor agonists and activators of protein kinase C, phorbol esters, increase Ca2+ sensitivity of contractile elements in vascular smooth muscle. To discover if protein kinase C is involved in the agonist-mediated Ca2" sensitization, we examined the effects of receptor agonists in the rat isolated aorta in which protein kinase C activity had been diminished by pretreatment with phorbol 12-myristate 13-acetate for 24 h.2 In the aorta with protein kinase C activity, a high concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 26 publications
4
29
2
Order By: Relevance
“…sensitization of contractile proteins in vascular smooth muscle (38,39), and this pathway is mediated by a rhoA-dependent process (40). We found here that basal active tonus was partly but significantly inhibited by Y-27632, a potent rho-kinase inhibitor.…”
Section: +supporting
confidence: 49%
“…sensitization of contractile proteins in vascular smooth muscle (38,39), and this pathway is mediated by a rhoA-dependent process (40). We found here that basal active tonus was partly but significantly inhibited by Y-27632, a potent rho-kinase inhibitor.…”
Section: +supporting
confidence: 49%
“…In similar to GTP g S, phenylephrine and histamine enhanced the Ca 2+ -induced contractions without being modi®ed by the PKC inhibitors. While the possibility cannot ruled out that some receptor agonists may generate enough diacylglycerol to activate PKC to a level similar to that activated by phorbol esters and result in Ca 2+ sensitization through the PKC-dependent pathway, our conclusion that PKC has only a minor role, if any, in agonist-induced Ca 2+ sensitization is consistent with the results obtained in PKC-downregulated rat aorta (Hori et al, 1993). Therefore, it seems likely that phenylephrine and histamine also caused Ca 2+ sensitization through a PKCindependent pathway.…”
Section: Casupporting
confidence: 81%
“…It has been suggested that there are two pathways for Ca 21 sensitization in vascular smooth muscle: one is protein kinase C (PKC)-dependent and activated by phorbol esters, and the other is PKC-independent and activated by receptor agonists (26). Thus, it also remains to be clarified whether PKC is involved in the muscarinic Ca 2+-sensitizing effect in intestinal smooth muscle.…”
Section: Discussionmentioning
confidence: 96%